Bus route design in small demand areas - Černá, Anna; Černý, Jan; Přibyl, Vladimír (Transport, 2011)
The paper deals with the situation when a low populated area is in need of public transport service. It is necessary to design a bus route, passing through the area and meeting the accessibility and efficiency requirements. The article presents a mathematical formulation of the problem in terms of the network theory together with two exact and several heuristic methods for finding a solution. The paper describes that the problem is NP-hard, and therefore computing experience is outlined.First Published Online: 05 Oct 2011